Risk Factors for Metastatic Castration-Resistant Prostate Cancer (CRPC) Predict Long-Term Treatment with Docetaxel - Kawahara, Takashi (Public Library of Science, 2012)
PURPOSE: For patients with metastatic castration-resistant prostatic cancer (mCRPC), docetaxel plus prednisone leads to superior survival and a higher response rate compared with mitoxantrone plus prednisone. We analyzed the efficacy of long-term treatment with ≥10 cycles of docetaxel, and validated the risk group classification in predicting overall survival (OS) in Japanese patients with mCRPC. PATIENTS AND METHODS: Fifty-two patients with mCRPC were administered 55 mg/m(2) docetaxel and 8 mg dexamethasone, every 3 or 4 weeks, simultaneously with hormonal therapy and daily oral dexamethasone. They were divided into two groups, short-term (9 or fewer cycles) and long-term (10 or more cycles). Four risk factors including the presence of anemia, bone metastases, significant pain and visceral metastases were utilized for the risk group classification. RESULTS: Fourteen patients (27%) had an elevation of PSA in spite of docetaxel treatment, while 23 patients (44%) had a decline in PSA level, including 9 patients (17%) whose PSA level declined by ≥50%. The median duration of OS after the initiation of this therapy was 11.2 months in the short-term group and 28.5 months in the long-term group. The good risk group showed a significant difference in OS compared with the intermediate and poor risk groups (P<0.001). The median number of cycles of treatment was 14, 4 and 3 for each risk group, respectively (p<0.01). CONCLUSIONS: The present study indicated that ≥10 cycles of this docetaxel therapy can significantly prolong survival in Japanese men with CRPC. This risk group classification for men with mCRPC at the initiation of this chemotherapy is useful.